U and Th thin film neutron dosimetry for fission-track dating: Application to the age standard Moldavite - Iunes, P. J.; Bigazzi, G.; Hadler Neto, J. C.; Laurenzi, M. A.; Balestrieri, M. L.; Norelli, P.; Osorio Araya, A. M.; Guedes, S.; Tello S., C. A.; Paulo, S. R.; Moreira, P. A.F.P.; Palissari, R.; et al. (My University, 2005)
Neutron dosimetry based on U and Th thin films was used for fission-track dating of the age standard Moldavite, the central European tektite, from the Middle Miocene deposit of Jankov (southern Bohemia, Czech Republic). Our fission-track age (13.98±0.58Ma) agrees with a recent 40Ar/39Ar age, 14.34±0.04Ma, based on several determinations on Moldavites from different sediments, including the Jankov deposit. This result indicates that the U and Th thin film neutron dosimetry represents a reliable alternative for an absolute approach in fission-track dating. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Fission-track dating; Moldavite; Neutron dosimetry; Th thin film; U thin film